2016
DOI: 10.1016/s1470-2045(16)30098-5
|View full text |Cite|
|
Sign up to set email alerts
|

Nivolumab alone and nivolumab plus ipilimumab in recurrent small-cell lung cancer (CheckMate 032): a multicentre, open-label, phase 1/2 trial

Abstract: There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/118215/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

35
966
4
18

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,127 publications
(1,023 citation statements)
references
References 35 publications
35
966
4
18
Order By: Relevance
“…However, the majority of patients either do not respond upfront or eventually progress. Combination immunotherapies with agents such as CTLA-4 inhibitors may enhance efficacy and responses but also substantially increase toxicity, as reported in patients with melanoma or lung cancer (22,23). Despite the successes of PD-1 checkpoint blockade across various malignancies, an urgent need still exists to improve outcomes and survival for patients with advanced solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of patients either do not respond upfront or eventually progress. Combination immunotherapies with agents such as CTLA-4 inhibitors may enhance efficacy and responses but also substantially increase toxicity, as reported in patients with melanoma or lung cancer (22,23). Despite the successes of PD-1 checkpoint blockade across various malignancies, an urgent need still exists to improve outcomes and survival for patients with advanced solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint receptors such as PD-1 and CTLA-4, whose blockade through mAbs recently showed significant response rates in otherwise pretreated patients, 11,30 are upregulated on activated T cells. In the tumor microenvironment, T cells expressing PD-1 have been identified as clonal expansion of tumor reactive T cell populations, thus representing functionally important components in order to eliminate tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of the smallcell lung cancer cohort included 216 patients allocated in three different schedules: nivolumab alone or in combination with ipilimumab at two different doses. Anti-tumour activity in small-cell lung cancer patients was seen in all schedules (15). Confirmed responses were observed in 10% (95% CI: 5-18) of patients with nivolumab 3 mg/kg, 23% (13-36%) with nivolumab 1 mg/kg plus ipilimumab 3 mg/kg, and 19% (9-31%) with nivolumab 3 mg/kg plus ipilimumab 1 mg/kg.…”
mentioning
confidence: 85%
“…Notably in the CheckMate 032 trial an essentially equal likelihood of responses was observed in PD-L1 negative and PD-L1 positive small-cell lung cancer tumors, not only in the nivolumab cohort but also in the combination cohort, suggesting that PD-L1 does not enrich for response in small-cell lung cancer (15). Whether PD-L1 expression is of any predictive utility in small-cell lung cancer must await analysis in a larger population.…”
mentioning
confidence: 99%
See 1 more Smart Citation